Comparison of Two Immunoturbidimetric C-Reactive Protein Assays on the Same Automated Analyzer - Mehmet Akif Bildirici (Journal of Turkish Clinical Biochemistry, 2026)
Objective: To compare the analytical performance of 2 immunoturbidimetric C-reactive protein (CRP) reagents using the same automated analyzer and to evaluate whether an alternative reagent provides clinically acceptable results. Methods: This prospective method-comparison study used 44 residual serum samples. C-reactive protein levels were measured on a Beckman Coulter AU5800 clinical chemistry analyzer using the original Beckman Coulter reagent and an alternative Archem reagent. Method comparison was performed in accordance with CLSI EP09-A3 guidelines using percentage difference plots and Passing–Bablok regression analysis. Precision was evaluated based on CLSI EP15-A3 recommendations. Acceptable bias was defined as 23.4% according to the EFLM Biological Variation Database. Results: The mean percentage difference between the methods was −15.4% (95% CI: −18.0 to −12.9), which was within the predefined acceptable bias limits. Passing–Bablok regression analysis showed a slope of 0.78 (95% CI: 0.73-0.81) and an intercept of 0.56 (95% CI: 0.36-0.83), indicating proportional and constant differences between the methods. Both reagents demonstrated acceptable within-run and between-run precision. Within-run precision values exceeded the manufacturer’s specifications, whereas between-run precision results were consistent with the reported values. Conclusion: Despite the presence of proportional and constant differences, the alternative CRP reagent demonstrated clinically acceptable analytical comparability within biological variation–based limits. These findings support its potential use in routine laboratory practice, provided that the same reagent is consistently used for patient follow-up.